Re-designing ESP Syllabus Design for Pre-Service Teachers in the Physical Education of Elementary Teacher Programs - Rahman, Aam Ali; Setyarini, Sri; Purnawarman, Pupung (Mimbar Sekolah Dasar, 2024)
Technology-cultivated learning opens opportunities to acquire knowledge from various resources. However, languages become a barrier for non-English major students. ESP allows students to familiarise their English with their specific subject. Nevertheless, less research develops PE lessons that integrate specific sports vocabulary and communication skills relevant to the activity. Thus, this study aims to explore the needs of the Physical Education of Elementary Teacher Program (PE-ETP) pre-service teachers. One hundred eighty-eight students participated in this study. The survey, focus group discussion, and interview formulated the findings. The result shows that 42% (80 participants) considered ESP very important as part of the curriculum. 56% (105 participants) consider it essential. Only 2% (3 participants) stated that ESP is not important and cannot be part of the curriculum. Further, eight possible topics were offered in developing ESP courses for the PE-ETP. The topics are teaching PE using English (92.02%), academic English for sports (87.77%), athlete communications (86.70%), referee communications (87.77%), coach communications (90.96%), sports category (91.49%), sports terms (92.55%) and Physiology terms (88.83%). The topics can be developed into specific course units in syllabus design.